Asian diasporas : cultures, identities, representations - Goh, Robbie B. H., 1964-; Wong, Shawn, 1949- (Honk Kong University Press, 2004)
The essays in this volume view Asian diasporic movements in the context of globalization and global citizenship, in which multiple cultural allegiances, influences and claims together create complex negotiations of identity.